Business process orientation construct analysis in companies in the Republic of Macedonia - Mijoska belshoska, Marina; Levkov, Nikola (MIPRO Croatian Society, 2015)
In today's global and continuously changing environment, companies are pressured to become more flexible, fast responding, customer oriented and to follow the fast technological development. To achieve these goals they should become business process oriented. Business process orientation (BPO) and process thinking help management to leverage the use of information and communication technologies (ICT) and the Internet, and hence to implement e-business more successfully. E-business strategies have made the need of streamlining, integrating and automating business processes even more pressing. Hence, efficient business processes and higher levels of process orientation are become elementary for organization's success in e-business environment. Due to the potential of e-business technologies and organizational transformation towards process oriented organization in dynamic environment, the goal of this paper is to analyze business process orientation of Macedonian companies in selected industries and to estimate their level of business process maturity. For this purpose an empirical research was conducted based on the previously prepared questionnaire interviewing managers in Macedonian companies in the banking, telecommunication and IT sector.
Keywords: business process, e-business, interview, business process orientation